Reliability Aspects in Snubber Circuit for Industrial Power Applications - Dwivedi D.; Singh S.; Sarita K.; Saket R.K.; Sanjeevikumar P. (My University, 2025)
Snubbers are a crucial component of power electronics. Snubbers are compact networks of components in power-switching circuits whose purpose is to regulate the effects of circuit reactances. Snubbers improve switching circuit performance by increasing reliability, efficiency, switching frequency, small size, lightweight, and EMI. This chapter outlines some of the numerous passive snubber types, their applications, methods of operation, technical specifications, and limits. The simulation results are provided for snubber validation. Further the reliability assessment of various types of passive snubber circuits with their relevance in the context of modern power system applications. © 2024 by The Institute of Electrical and Electronics Engineers, Inc. All right reserved.